Go-Food Digital Application and Its Role in Promotional Communication Strategy - Aprih Santoso; D.C. Kuswardani; Wyati Saddewisasi; Maria Assumpta Wikantari (International Journal of Artificial Intelligence Research, 2022)
This study aims to dig deeper into the Go-Food application-based online promotional tricks for the Bandeng Presto cluster in Semarang city. This is a case study with a qualitative approach. Data collection techniques with interviews, observation, documentation and literature study. The number of informants was 57 informants. The results of this study indicate that online promotion tricks are based on the Go-Food application in the Bandeng Presto cluster in the city of Semarang. has benefits, namely: increasing the number of consumers, expanding the market, increasing income, as a promotional medium, time efficiency and increasing credibility, while the disadvantages can be overcome by technology development carried out on the Go-Food application. Thus the advantages gained by online promotion tricks based on the Go-Food application are more than the losses, so it can be concluded that the online promotional tricks based on the Go-Food application are suitable for use by the Bandeng Presto cluster in the city of Semarang